2007
DOI: 10.1002/elan.200603790
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Acid Doped Polyaniline Nanotubes for Oligonucleotide Sensors

Abstract: Template-free, self-assembled polyaniline (PANI) nanotubes were prepared in a solution of poly(methyl vinyl etheralt-maleic acid) (PMVEA) by oxidative polymerization using ammonium persulfate as the oxidant. The weight ratio of the polymeric acid to aniline in the solution had a significant effect on the size of the polyaniline nanotubes as determined by SEM. The outer diameter of the nanotubes increased from 65 nm to 160 nm with increased levels of PMVEA in the reaction solution from 1 to 4 wt/v%. The PANI/PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 48 publications
0
45
0
2
Order By: Relevance
“…One of the exceptions is conducting polyaniline [3][4][5], for which researchers are looking with considerable interest for applications in organic electronic devices, such as organic light-emitting diodes (OLEDs) [6,7], Schottky barrier diodes [8,9], organic electrodes [7], electro-chromic displays [10], sensors [11,12] and energy storage devices, including supercapacitors and batteries [13][14][15]. Although polyaniline has large potential as a future material in next-generation electronic devices, the low electrical conductivity and stability of polyaniline, as well as its solubility have limited its applications [16] Despite the interest of polyaniline for applications in the area of sensors [17,18] there are not enough data and investigations on the piezoresistive properties of this polymer.…”
Section: Introductionmentioning
confidence: 99%
“…One of the exceptions is conducting polyaniline [3][4][5], for which researchers are looking with considerable interest for applications in organic electronic devices, such as organic light-emitting diodes (OLEDs) [6,7], Schottky barrier diodes [8,9], organic electrodes [7], electro-chromic displays [10], sensors [11,12] and energy storage devices, including supercapacitors and batteries [13][14][15]. Although polyaniline has large potential as a future material in next-generation electronic devices, the low electrical conductivity and stability of polyaniline, as well as its solubility have limited its applications [16] Despite the interest of polyaniline for applications in the area of sensors [17,18] there are not enough data and investigations on the piezoresistive properties of this polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques have been used to synthesize PANI nanostructure such as stirring [6][7][8], static placement, [9] sonication [10][11][12], and emulsion polymerization [13][14][15][16]. Particularly, conducting polymer nanotubes and nanofibers have received growing interest in recent years due to their unique properties and promising potential applications in nanodevices [17][18][19][20][21]. The investigation of nanostructured conducting polymers has great importance for both scientific and technological points of view.…”
Section: Introductionmentioning
confidence: 99%
“…The hybridization events were detected by differential pulse voltammetry (DPV) measurement using methylene blue as an indicator and a detection limit of 1.0 pM was reported. Zhang et al demonstrated a templatefree method to prepare polyaniline nanotubes from a solution containing poly(methyl vinyl ether alt-maleic acid) (PMVEA) and using ammonium persulfate as the oxidant [118]. The obtained nanotubes were deposited onto a glassy carbon electrode, followed by grafting of amino-modified ODN probes onto the residual carboxylic acid functionalities on the nanotubes.…”
Section: Dna Sensors Based On Polyaniline and Its Derivativesmentioning
confidence: 99%